HEART RATE VARIABILITY IN HEALTHY POPULATION - Khan, Muhammad Alamgir; Hussain, M Mazhar; Aleem, Shoaib Bin (Pakistan Journal of Physiology, 2010)
Background: Heart rate variability has been considered as an indicator of autonomic status. Little work has been done on heart rate variability in normal healthy volunteers. We aimed at evolving the reference values of heart rate variability in our healthy population. Methods: Twenty-four hour holter monitoring of 37 healthy individuals was done using Holter ECG recorder ‘Life card CF’ from ‘Reynolds Medical’. Heart rate variability in both time and frequency domains was analysed with ‘Reynolds Medical Pathfinder Digital/700’. Results: The heart rate variability in normal healthy volunteers of our population was found in time domain using standard deviation of R-R intervals (SDNN), standard deviation of average NN intervals (SDANN), and Square root of the mean squared differences of successive NN intervals (RMSSD). Variation in heart rate variability indices was observed between local and foreign volunteers and RMSSD was found significantly increased (p<0.05) in local population. Conclusions: The values of heart rate variability (RMSSD) in healthy Pakistani volunteers were found increased compared to the foreign data reflecting parasympathetic dominance in our population.